1996
DOI: 10.1016/s1074-7613(00)80252-6
|View full text |Cite
|
Sign up to set email alerts
|

TNF-Dependent Recruitment of the Protein Kinase RIP to the TNF Receptor-1 Signaling Complex

Abstract: The death domain of tumor necrosis factor (TNF) receptor-1 (TNFR1) triggers distinct signaling pathways leading to apoptosis and NF-kappa B activation through its interaction with the death domain protein TRADD. Here, we show that TRADD interacts strongly with RIP, another death domain protein that was shown previously to associate with Fas antigen. We also show that RIP is a serine-threonine kinase that is recruited by TRADD to TNFR1 in a TNF-dependent process. Overexpression of the intact RIP protein induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
802
2
6

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,077 publications
(828 citation statements)
references
References 35 publications
18
802
2
6
Order By: Relevance
“…Interestingly, these cells retain TNF-mediated JNK activation, suggesting that RIP may not be directly involved in the activation of JNK (Kelliher et al, 1998). This observation poses a problem in explaining earlier results, where Hsu et al (1996) have shown that dominant negative mutants of RIP block activation of both NF-kB and JNK. This model also does not explain how a kinase-defective RIP mutant restores the NF-kB inducibility in a RIPde®cient JURKAT clone (Ting et al, 1996).…”
Section: Survival Signals Transduced By Tnf-rimentioning
confidence: 80%
“…Interestingly, these cells retain TNF-mediated JNK activation, suggesting that RIP may not be directly involved in the activation of JNK (Kelliher et al, 1998). This observation poses a problem in explaining earlier results, where Hsu et al (1996) have shown that dominant negative mutants of RIP block activation of both NF-kB and JNK. This model also does not explain how a kinase-defective RIP mutant restores the NF-kB inducibility in a RIPde®cient JURKAT clone (Ting et al, 1996).…”
Section: Survival Signals Transduced By Tnf-rimentioning
confidence: 80%
“…The stimulation of TNF-R1 with TNF leads to the interaction of TNF-R1-associated death domain protein (TRADD) 19 and RIP1 20 with the TNF-R1 signalling complex (Figure 2). This is followed by the recruitment of a number of E3 ubiquitin ligases to RIP1, including TNF receptor-associated factor 2 (TRAF2) or TRAF5 and the cellular inhibitor of apoptosis proteins (cIAPs) cIAP1 and cIAP2 resulting in the formation of Complex I.…”
Section: Rip1 and Tnf Signalling: Inflammation Versus Apoptosismentioning
confidence: 99%
“…TNF binding induces receptor aggregation, which results in the recruitment of a number of cytoplasmic signaling proteins to two distinct TNFR complexes (Rothe et al, 1994(Rothe et al, , 1995bHsu et al, 1995Hsu et al, , 1996aShu et al, 1996). One of these molecules is TNF receptor associated factor 2 Figure 1 The mammalian stress-activated MAP kinase modules.…”
Section: Tnf Receptor Associated Factors (Trafs)mentioning
confidence: 99%